Modernity and the reinvention of tradition backing into the future - Prickett, Stephen 1939-2020 (Cambridge Univ. Press, 2009)
An original investigation into how tradition has developed over the centuries into our modern understanding of the term.
Includes bibliographical references
Keywords: Geschichte 1700-1800; Geschichte 1800-1900; Geistesgeschichte; Geschichte 1700-1900; Geschichte; Tradition (Philosophy) -- History; Tradition (Theology) -- History of doctrines; Literature, Modern -- 19th century -- History and criticism; Literature, Modern -- 18th century -- History and criticism; Theologie; Begriff; Tradition; Philosophie; Literatur; Europa